2188. Effectiveness of a Risk-Stratified Measles Post-Exposure Prophylaxis Strategy to Prevent Nosocomial Transmission. (26th November 2018) - Seah, Valerie Xue Fen; Chong, Chia Yin; Tan, Natalie Woon Hui; Thoon, Koh Cheng; Yung, Chee Fu
Abstract: Background: Measles is a highly contagious disease and nosocomial outbreaks have been documented. Pediatric hospitals are particularly at risk due to the concentration of susceptible patients such as infants <12 months old or with immunocompromised status. Effective strategies to control nosocomial measles transmission will be critical for successful measles elimination. We reviewed the impact of our hospital's approach for post-exposure prophylaxis (PEP) against measles. Methods: We extracted details of all measles intra-hospital exposure events in our pediatric hospital in April 2016 to December 2016. For this analysis, we only included close contacts who were defined as patients within the same cubicle as the measles index case for any duration prior to the index case isolation. All close contacts were followed up with a telephone call to check if they developed fever or rash after the incubation period. In May 2016, we implemented measles PEP [(measles, mumps, and rubella (MMR) vaccine or immune globulin (IG)) for close contacts in accordance to their age and immunity status. Details of events pre-vs. post-PEP implementation were analysed. Results: Prior to PEP implementation, there were two exposure events resulting in eight close contacts, of which seven (87.5%) had no MMR vaccination and one had received a single dose. Subsequently, two (25%) developed confirmed measles approximately 2 weeks post-exposure. Post-PEP implementation, there were four exposure events resulting in 14 close contacts, of which all had no MMR vaccination. Five patients were positive for measles serology. Measles PEP was given to eight patients, where seven received IG and one (7.1%) had MMR vaccination. At follow-up, two of the 14 close contacts reported fever during the incubation period but none developed measles. One was already known to be measles serology positive and the second who was given IG was diagnosed with unresolved RSV. Conclusion: Implementation of measles PEP in our hospital prevented secondary nosocomial transmission amongst susceptible close contacts in the same cubicle. Disclosures: All authors: No reported disclosures.